The long non‐coding RNA Paupar promotes KAP1‐dependent chromatin changes and regulates olfactory bulb neurogenesis. (16th April 2018) - Pavlaki, Ioanna; Alammari, Farah; Sun, Bin; Clark, Neil; Sirey, Tamara; Lee, Sheena; Woodcock, Dan J; Ponting, Chris P; Szele, Francis G; Vance, Keith W
Abstract: Many long non‐coding RNAs (lncRNAs) are expressed during central nervous system (CNS) development, yet their in vivo roles and mechanisms of action remain poorly understood. Paupar, a CNS‐expressed lncRNA, controls neuroblastoma cell growth by binding and modulating the activity of transcriptional regulatory elements in a genome‐wide manner. We show here that the Paupar lncRNA directly binds KAP1, an essential epigenetic regulatory protein, and thereby regulates the expression of shared target genes important for proliferation and neuronal differentiation. Paupar promotes KAP1 chromatin occupancy and H3K9me3 deposition at a subset of distal targets, through the formation of a ribonucleoprotein complex containing Paupar, KAP1 and the PAX6 transcription factor. Paupar ‐KAP1 genome‐wide co‐occupancy reveals a fourfold enrichment of overlap between Paupar and KAP1 bound sequences, the majority of which also appear to associate with PAX6. Furthermore, both Paupar and Kap1 loss‐of‐function in vivo disrupt olfactory bulb neurogenesis. These observations provide important conceptual insights into the trans ‐acting modes of lncRNA‐mediated epigenetic regulation and the mechanisms of KAP1 genomic recruitment, and identify Paupar and Kap1 as regulators of neurogenesis in vivo . Synopsis: The formation of an RNP complex containing a long non‐coding RNA (lncRNA), a chromatin regulator and transcription factor illustrates how a single nuclear lncRNA can regulate transcription of multiple target genes in trans . The CNS‐expressed lncRNA Paupar interacts with the TRIM28/TIF1/KAP1 chromatin regulatory protein. Paupar acts in trans to promote KAP1 chromatin occupancy and H3K9me3 deposition at a subset of bound target sites. Paupar regulation in trans requires the formation of a ribonucleoprotein complex containing Paupar, KAP1 and non‐KRAB‐ZNF transcription factors such as PAX6. Paupar and KAP1 function as regulators of olfactory bulb neurogenesis in vivo . Abstract : Complex formation between a long non‐coding RNA (lncRNA), a chromatin regulator and transcription factor illustrates how nuclear lncRNAs can regulate transcription in trans .